Fixing the leak: unemployment incidence before and after the 2006 reform of unemployment benefits in Germany - Stephan Dlugosz; Gesine Stephan; Ralf A. Wilke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
From 2002-2004, the German government passed several laws that curtailed the generosity of the unemployment compensation system. One of the most ambitious changes was a considerable reduction in unemployment benefit entitlement lengths for older unemployed, which was effective during 2006 and 2007. We apply a difference-in-differences approach to show that the highly disputed reform induced a considerable decline in unemployment incidence among older workers. It thus sealed an important leak in the unemployment insurance system. Furthermore, we find a strong anticipation effect; unemployment entries of elderly workers peaked during the months preceding the reform.
Keywords: J63; J65; 330; unemployment incidence; policy evaluation; administrative data; Arbeitslosenversicherung; Hartz-Reform; Wirkungsanalyse; Arbeitslosigkeit; Ältere Arbeitskräfte; Deutschland